Diversification for sustainable and resilient agricultural landscape systems - Reckling, M.; Watson, C.; Whitbread, Anthony M.; Helming, K. (Springer, 2023)
This virtual issue comprises papers that address diversification for providing sustainable solutions at different scales from cropping and grassland to food systems. The authors investigated processes in case studies at the landscape scale where synergies and trade-offs between social and environmental objectives become the most tangible. Contributions from all continents highlighted regional specificities related to diversification and include research from natural and social sciences, with inter- and transdisciplinary approaches including synthesis of knowledge (reviews), empirical studies with experiments as well as assessments with interviews in case studies: Model-based design of crop diversification, the role of digitalization for achieving sustainability in the European context, ecological engineering for rice pest suppression in China, the role of cereal species mixtures in Ethiopian smallholder farmers, diversified planting in arid irrigation areas in northwestern China, integration of legumes in European and Canadian cropping systems, screening of native forage legumes for northern Swedish grassland systems, cropping system diversification of smallholder farmers in south-central Bangladesh, identification of how farmers imagine diversified landscapes in southern Idaho in the US, farm diversification affecting impacts from COVID-19 across Europe, the role of diversified farming in Mato Grosso Brazil, diversification and soil management measures in Germany, value chain formation for the scaling of crop diversification, and the design process with farmers and scientists for the transition toward legume-supported farming in Europe. A key finding from these examples is that agricultural intensification has led to the simplification of cropping systems and landscapes in terms of species diversity and ecosystem function. To instead move towards sustainable transformation, all system levels (i.e. from the plot, farm, landscape, governance and overall food systems) need to interact and reinforce each other for diversification to deliver the desired outcomes.